KOMUNIKASI NONVERBAL PEMERAN DALAM MEDIUM FILM(Analisis Semiotika Roland Barthes Pada Film Pendek Horor "Kangen") - Muhammad Fathan Ibadurrahman (2021)
This research is a semiotic study on a short horror film "Kangen". This study aims to find out the meaning behind nonverbal symbols in the form of body language such as head gestures, body gestures, hand gestures, foot gestures, as well as facial expressions of actors or actresses from each scene in the film. As well as analyzing the meaning of denotation, namely the visible or actual meaning, connotation, which is a figurative meaning that is subjective, and myth, which tends to mystical things resulting from nonverbal communication gestures and expressions of a character actor in the horror short film "Kangen" using Roland Barthes' semiotic analysis. This study uses a descriptive qualitative methodology with Roland Barthes semiotic analysis based on the concepts of gestures from experts that researchers get from books, journals, and other scientific literature to parse and explain the meaning in the form of denotation, connotation, and also the myth of each message that is conveyed. conveyed through body language. The results showed that nonverbal symbols in the short film "Kangen" were represented through head, hand, body, foot, and facial expressions. The purpose of using gestures in this film is more to emphasize emotions, repeat ideas and replace verbal messages (dialogue). The meaning of denotation is the actual meaning as depicted in the film. The connotation meaning of gesture symbols in the scenes is the result of the researcher's own interpretation. Then the meaning of myth, because the short film "Kangen" is a horror genre film, the mythical meaning of the symbols in the film "Kangen" is more inclined to scenes that are mystical, superstitious, and unreasonable. Some of them lead to social norms. Suggestions that researchers can give for further research are to analyze gestures from films originating from outside Indonesia, because the meaning of gestures and expressions from each country is different depending on the local culture. Then for practitioners to use symbols, gestures and more expressions so that the delivery of messages and appreciation of the story is deeper.